Control algorithm for two-tank system using multiparametric programming - Zakaria, A.; Mid, E.C.; Mohamed, M.F.; Hussin, M.H.M.; Shaari, A.S.; Ruslan, Eliyana; Hadi, Dayanasari; Masri, M. (2023)
The two-tank system consists of two connected tanks, where the goal is to control the liquid levels in both tanks by manipulating the inflow rates. This study proposes a control algorithm for a two-tank system based on multiparametric programming. In this work, the flow rate is determined using multiparametric programming. The simulation studies demonstrate the proposed work's effectiveness by comparing its performance with and without noise. Results show accurate and robust regulation of liquid levels, minimizing control effort and making it suitable for systems with dynamic variations or parameter uncertainties. In conclusion, the implementation of multiparametric programming is able to estimate the value of the output for the control algorithm of the two-tank system.